A monetary analysis of foreign exchange marketdisequilibrium in Fiji. (14th February 2012) - Ahmad, Shabbir; Shamsuddin, Abul; Treadgold, Malcolm
This paper evaluates a monetary model of foreign exchange market pressure in Fiji using the autoregressive distributed lag bounds testing methodology. The results suggest that if the monetary authorities in Fiji fix the exchange rate, they lose the ability to implement an independent monetary policy through control of central bank credit. Stronger monetary control is regained to the extent that pressure in the foreign exchange market is relieved through exchange rate movements rather than reserve movements.